Galery, Library, Archive, and Museum (GLAM) sebagai upaya transfer informasi - Lasenta Adriyana; Dwi Fitrina C (Shaut Al-Maktabah : Jurnal Perpustakaan, Arsip dan Dokumentasi, 2017)
In the era of information, galery, library, archive and museum (GLAM) is a unity which can not be separated. There are several reasons for GLAM to stand separately, but in the rapid growing information, it has cultivated new communications and information technologies that can unite the work of all these institutions. Released GLAM has the same destination, will be in Indonesia can not be united because it has different types of collections, and policies. This article concludes (1). GLAM has not been able to stay in one concept in Indonesia because of the different institutions has different policies. (2) The institution that oversees the collection of GLAM as a cultural heritage in Indonesia is Memory of the World (MOW). (3). GLAM has different types of collections and policies applied to users over their owned collections. (4). GLAM is one place that provides, manages, and transfers information to users.